Lycium Barbarum and Human Health 2015
DOI: 10.1007/978-94-017-9658-3_5
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Uses and Effects of Lycium Barbarum

Abstract: Lycium barbarum (LB) is one of the most intriguing medicinal plants in China. The beauty of its berries combined with the amount of beneficial effects assigned to it would logically make it a strong candidate for skin use, yet relatively few scientific publications address such application. Here, we will review the skin-related effects of oral and topical preparations of LB, based on the published scientific literature and work done in our own laboratory. We will also discuss the obstacles and opportunities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Plant substances can also have a beneficial effect on wound healing. Several experiments have demonstrated the stimulating effect of LBP on human skin fibroblasts and the role of directional fibroblast migration during wound healing has been explained (Wang et al, 2011;Song et al, 2013;Zhao and Bojanowski, 2015). These experiences justify the advisability of developing the production of cosmetics based on LBP.…”
Section: In the Cosmetics Industrymentioning
confidence: 95%
“…Plant substances can also have a beneficial effect on wound healing. Several experiments have demonstrated the stimulating effect of LBP on human skin fibroblasts and the role of directional fibroblast migration during wound healing has been explained (Wang et al, 2011;Song et al, 2013;Zhao and Bojanowski, 2015). These experiences justify the advisability of developing the production of cosmetics based on LBP.…”
Section: In the Cosmetics Industrymentioning
confidence: 95%
“…These authors found that, although this fruit is a strong candidate for dermatological use, few publications report its use. Some previously reported effects include antioxidant, antiinflammatory and immunomodulatory activities (Zhao, Bojanowski, 2015). However, no publications exist in the literature about a nanostructured system containing this extract.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the juice was able to protect against immunosuppression promoted by UV radiation. Zhao and Bojanowski (2015) described the dermatological uses of Lycium barbarum. These authors found that, although this fruit is a strong candidate for dermatological use, few publications report its use.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers and leaves of Lycium have also been used in ethnic medicine or local custom in soups and drinks due to their remarkable efficacy as antioxidants and antihypertensives owing to their high levels of flavonoids and polyphenols. 8,9 The high value of Lycium has further aroused research interest, and a wide range of compounds has been isolated, including polysaccharides, carotenoids, polyphenols, flavonoids, alkaloids, fatty acids, polyphenols and others. [10][11][12] The chemical diversity of secondary metabolites contributes to a strong foundation for many experiments for nutritional and clinical benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers and leaves of Lycium have also been used in ethnic medicine or local custom in soups and drinks due to their remarkable efficacy as antioxidants and antihypertensives owing to their high levels of flavonoids and polyphenols. 8,9…”
Section: Introductionmentioning
confidence: 99%